Evaluación del desarrollo rural y la conservación de recursos en la comunidad de terrabona, distrito Fernando Lores Río Amazonas. 2023 - Rojas Robledo, Nuvia Valeria Maggi (2024)
In this work, it can be seen that the knowledge that the inhabitants of Terrabona have about the investment projects that were carried out in their area results in 35% of the population recognizing the investment in a drinking water system for the community, and in the same way 40% recognize the drinking water project, and added to that, the investment generated by the company Tamshi, with the massive production of cocoa in the area of Fernando Lores in general, benefiting the surrounding communities in the same way. Already, 17.5% recognize the investments in drinking water and the emblematic aguaje project, which had been carried out by Rainforest for almost 20 years in the natural spaces of Fernando Lores. Finally, only 7.5% know about all the aforementioned projects. In terms of economic development, it can be seen that there is not much development in the TERRABONA area, but it can be noted that there is intervention by private entities that seek to promote the rational exploitation of natural resources and generate an opportunity for economic improvement for the inhabitants. However, we must take into account that private entities, whether companies or NGOs, work under their own guidelines and goals, limiting the contribution generated in the populations that they cover and invite to participate in their different projects, which makes the attempt at development seem somewhat lethargic and the attempts at growth in terms of resource conservation are poor.